Analisis Faktor - Faktor Yang Berperan Dalam Meningkatkan Kualitas Pada Transportasi Ojek Online di Jakarta - Marvin, Elang Alifian (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to explore information related to factors that play a role in improving the quality of online motorcycle taxi transportation in Jakarta. The method taken in conducting this research is a descriptive qualitative research method by searching for data in the form of literature articles related to research topics. From the analysis of several articles obtained the final results in the form of findings of several factors that play a role in improving the quality of online motorcycle taxi transportation, such as good communication to customers, relevant technology utilization, maximizing services, appropriate decision making in timeliness.